THE COMPLEXITY OF GOVERNANCE AND ETHICS OF POPULATION ADMINISTRATION SERVICES (KTP) ON PUBLIC SATISFACTION - Lia Sefiana; Ghania Saqifa Afwillah; Aulia Khusnul Nuraini; Dhanis Manda Saputri; Aulia Putri Hanastasya (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Population administration services are a fundamental form of public service, the quality of which is significantly influenced by the implementation of governance and service ethics among civil servants. This study aims to analyze the influence of governance and service ethics on public satisfaction with population administration services (ID cards) at the Population and Civil Registration Office of Kebumen Regency. This study employs an associative quantitative approach, focusing on a population of 2,376 residents from Wonoyoso Village, Kewarasan Subdistrict, Kebumen Regency, who have previously processed their ID cards. A sample of 96 respondents was selected using the Slovin formula with a 10% margin of error and a purposive sampling technique. The data collection instrument consisted of a closed-ended questionnaire using a five- point Likert scale, which had been tested for validity and reliability (Cronbach’s Alpha = 0.920). Data were analyzed using descriptive and inferential statistics through multiple linear regression analysis using SPSS. The results of the study indicate that governance significantly influences community satisfaction. Simultaneously, the two variables explain 49.5% of the variation in public satisfaction (R² = 0.495). The Spearman correlation test confirmed a strong positive relationship between governance and public satisfaction (r = 0.618), as well as between service ethics and public satisfaction (r = 0.669), with service ethics being the more dominant variable (β = 0.449). These findings imply that strengthening governance based on the principles of good governance and improving the service ethics of civil servants in a synergistic manner are important determinants that need to be prioritized by the Kebumen District Population and Civil Registration Office in its efforts to continuously improve public satisfaction with population administration services.